2001
DOI: 10.1073/pnas.151263098
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical emission line ratios for [Fe III] and [Fe VII] applicable to the optical and infrared spectra of gaseous nebulae

Abstract: Recent calculations of electron impact excitation rates and EinsteinA-coefficients for transitions among the 3d 6 levels of Fe III and among the 3d 2 levels of Fe VII are used to derive theoretical emission line ratios applicable to the optical and infrared spectra of gaseous nebulae. Results for [Fe III] are generated for electron temperatures Te ‫؍‬ 7,000 -20,000 K and densities Ne ‫؍‬ 10 2 -10 8 cm ؊3 , whereas those for [Fe VII] are provided for Te ‫؍‬ 10,000 -30,000 K and N e ‫؍‬ 10 2 -10 8 cm ؊3 . The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Figure 1 presents the region near the Balmer limit, where the Balmer continuum can be easily appreciated. The [Fe iii] density was derived from the I(4986)/I(4658) ratio and the computations by Keenan et al (2001). In Table 4 I compare the observed I( nm )/I(4658) ratios for a set of [Fe iii] lines with the predicted ratios by Keenan et al (2001) Table 4 it can be seen that the observed and predicted line ratios are in excellent agreement since the differences between them are of the order of their estimated errors.…”
Section: Temperatures and Densitiesmentioning
confidence: 87%
“…Figure 1 presents the region near the Balmer limit, where the Balmer continuum can be easily appreciated. The [Fe iii] density was derived from the I(4986)/I(4658) ratio and the computations by Keenan et al (2001). In Table 4 I compare the observed I( nm )/I(4658) ratios for a set of [Fe iii] lines with the predicted ratios by Keenan et al (2001) Table 4 it can be seen that the observed and predicted line ratios are in excellent agreement since the differences between them are of the order of their estimated errors.…”
Section: Temperatures and Densitiesmentioning
confidence: 87%
“…our knot 1), the estimated T e ([O ii]) can be up to ∼17% smaller. For n e ([Fe iii]), we used the line ratios tabulated by Keenan et al (2001), assuming T e = 12 000 K. Note that for the emission lines utilized, the dependence of the derived n e on the assumed temperature is negligible. Finally, n e ([Ar iv]) was derived using directly temden and assuming Notes.…”
Section: Physical Conditions Of the Ionized Gasmentioning
confidence: 99%
“…These Fe III transitions are also important tracers of Fe abundance in the case of H II regions and lowly ionized planetary nebulae, where they are often the only ionization state of Fe detected in the optical band. Garstang et al (1978) first noted the diagnostic potential of optical Fe III lines; subsequently, several authors have generated theoretical electron temperature (T e ) and density (N e ) dependent emission-line intensity ratios for this ion, and used these to determine plasma parameters for nebular sources (for example, Keenan et al 1993Keenan et al , 2001Bautista et al 2010, and references therein.). However, there are longstanding inconsistencies between electron densities derived from different Fe III ratios, as well as discrepancies with values of N e determined from other species such as OII, SII, and ClIII with similar ionization potentials to Fe III, which hence should originate in nearby regions of the nebular plasma.…”
Section: Introductionmentioning
confidence: 99%